Corrigendum to “Numerical studies of atomic three-step photoionization processes with non-monochromatic laser fields” - Lu, Xiaoyong; Wang, Lide; Li, Yunfei (Chinese physics B, 2024)
The Eq. (6) about the time correlation function of the chaotic field model is corrected, along with the corresponding statement. The enlargement factors of ρ 33, B and ρ ion,B in the legends of Figs. 2(b), 2(c) and 2(d) are corrected. These corrections do not affect the conclusions of the work [ Chin. Phys. B 31 063203 (2022)].